2002
DOI: 10.1006/exer.2002.2039
|View full text |Cite
|
Sign up to set email alerts
|

UVA Light In vivo Reaches the Nucleus of the Guinea Pig Lens and Produces Deleterious, Oxidative Effects

Abstract: The possible role of ultraviolet light in the formation of cataract is not well understood. In this study, guinea pigs were exposed to a chronic, low level of UVA light (0.5 mWcm(-2), 340-410 nm wavelength, peak at 365 nm) for 4-5 months. It is known that the lens of the guinea pig possesses unusually high levels of the UVA chromophore NADPH. In a preliminary analysis, it was found that isolated guinea pig corneas transmitted 70-90% of 340-400 nm light, and that UVA radiation was able to penetrate deep into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 75 publications
2
41
1
3
Order By: Relevance
“…The low UVR-B penetration into the lens (Lo¨fgren & So¨derberg 2001) further argues against UVR-B-induced nuclear cataract. UV-A radiation on the other hand reaches the lens nucleus and is suggested as one cause for human nuclear cataract (Giblin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The low UVR-B penetration into the lens (Lo¨fgren & So¨derberg 2001) further argues against UVR-B-induced nuclear cataract. UV-A radiation on the other hand reaches the lens nucleus and is suggested as one cause for human nuclear cataract (Giblin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…UVR induces the accumulation of reactive oxygen species (ROS) which stimulates the secretion of hormones such as α-melanocytestimulating hormone (α-MSH) and adrenocorticotropic hormone (ACTH), endothelin-1(ET-1), as well as basic fibroblast growth factor (bFGF), stem cell factor (SCF) and immune factors [2,3]. These induced factors stimulate the expression of microphthalmiaassociated transcription factor (MITF) by acting melanocortin receptor 1 (MC1R), endothelin receptor (EDNR) and stem cell growth factor receptor (SCFR) on the melanin cell membrane through the pathway of cyclic adenosine monophosphate protein kinase A (cAMP-PKA) or nitric oxide/cyclic guanylate monophosphate protein kinase G (NO/cGMP-PKG).…”
Section: Introductionmentioning
confidence: 99%
“…Godar et al (39) and Ortwerth et al (40) demonstrated that ϳ0.8 -1.1 mJ/cm 2 of UVA can reach the lens surface in the midday sun, but only 0.06 -0.08 mJ/cm 2 of UVB light reaches the lens under the same conditions (39,41,42). Dillon et al (42) demonstrated that, unlike UVB light, UVA light can penetrate the nucleus of the aged human lens, where most photooxidation has been observed (43,44).…”
mentioning
confidence: 99%